Photovoltaic Modules with the Look and Feel of a Stone Façade for Building Integration. Issue 5 (27th July 2021) - Morlier, Arnaud; Lim, Bianca; Blankemeyer, Susanne; Schulte-Huxel, Henning; Witteck, Robert; Daschinger, Thomas; Bräunig, Sonja; Köntges, Marc; Brendel, Rolf
Abstract : The vast majority of photovoltaic (PV) modules feature a glass pane on the front side. Even specialized products for integration into building skins usually have the look and feel of (colored) glass panes. Herein, PV modules that have the look and feel of natural stone façades are presented. This is achieved by either replacing the front glass pane of PV modules with a stone veneer sheet or by laminating veneers of natural stones onto the front glass pane of PV modules, allowing retrofitting of standard PV modules. A wide variety of stones can be integrated in this way into PV modules. One‐cell PV modules are fabricated using 156 mm × 156 mm silicon solar cells and different stone veneers, and power conversion efficiencies up to 11.2% are achieved, compared to 20.7% for a control PV module. Large‐area demonstrator PV modules with a size of 1220 mm × 610 mm are also fabricated using 49 half‐cells that yield up to 8.5% efficiency. The impact of the inhomogeneity of the stone veneers on the performance of the PV modules is analyzed and measures are suggested to reduce the efficiency losses caused by the application of the stone veneers. Abstract : Thin stone veneers are applied to the front side of photovoltaic modules. This results in modules that look and feel like stone cladding for facades. The performance loss for different stone materials is determined and it is found that up to 50% of the original module efficiency can be retained. Options are proposed for further efficiency improvement.